Theory and Practice of Participatory Action Research and Learning with Cluster Marketing Groups in Mindanao, Philippines - Murray-Prior, Roy; Batt, Peter; Rola-Rubzen, Maria Fay; Concepcion, S.; Montiflor, M.; Axalan, J.; Real, R.; Lamban, R.; Israel, F.; Apara, D.; Bacus, R. (International Society of Horticultural Science, 2013)
Researching and developing new arrangements for marketing smallholder products in the transitional economies is complex and requires an agribusiness systems approach. One approach to addressing complex problems is for researchers to facilitate an action learning process with farmers and market intermediaries, while using an action research process to investigate the factors that enhance the chances of success for farmer groups. This paper reviews the literature on action learning, action research and participatory processes in an attempt to clarify some of the terminology and define the similarities and differences. It outlines research into a framework to improve the effectiveness and resilience of cluster marketing groups through the application of these processes to smallholder vegetable chains in Mindanao, the southern Philippines.